. Place of the synergetic paradigm in legal and criminological researches - Лукашевич, С. Ю.; Груба, Д. І. (Theory and practice of jurisprudence, 2016)
Possibilities of application of provisions and the principles of a synergetic paradigm both methodological bases of legal researches in general, and criminological in particular are analysed. The assumption that on the basis of synergetic approach probably essential improvement of system of the prevention and counteraction of crime both on all-social, and on special and criminological levels is stated.